HUBUNGAN ANTARA TINGKAT KECEMASAN DAN HASIL BELAJAR MATEMATIKA PADA SISWA SMP ISLAM DI KOTA PALU - Nurhalida Sartika (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2019)
Some previous studies has showed that math anxiety correlated with mathematics learning outcomes. This study involved 181 students grade 7th of Islamic Junior High School in Palu. The method of this research is quantitative research method with survey. The design of survey is a cross-sectional design. The results showed that: 1) There was not significant negative relationship between math anxiety with mathematics learning outcomes (r = -0.052); and 2) There were not significant differences in students' mathematics learning outcomes based on the level of math anxiety